Global meets local: typographic practices and the semiotic role of subtitling in the creation of parodies in Cypriot dialect on Internet texts - Papadima-Sophocleous, Salomi; Kourdis, Evangelos (My University, 2016)
The framework which governs subtitles and viewers’ comments is investigated in this study, through five film clips-parodies of the same movie, which are subtitled in the Cypriot dialect with different linguistic content every time. The study focuses on the semiotic role of subtitling and the examination of text content and meaning. Also, subtitle characteristics and typographic practices for the transcription of subtitles into a language system which lacks an official and widely accepted orthographic system are examined. As for the visual rendering of the Cypriot dialect in subtitling, the study proposes that the use of typography by fansubbers, facilitated by technology proliferation, often results in failure of legibility, cohesion and comprehension of the text, while projecting a sense of orality and improvisation. The main concluding remark is that subtitling is used as a semiotic tool in visual communication as it operates as a “semiotic switch” in the expected production of semiosis by the language of the text and the production of semiosis by the subtitles.
Keywords: Cypriot dialect; Mass culture; Parodies; Semiotics; Subtitling; Typography